Tipificación de Candida y antifungigrama en muestras de secreción vaginal de pacientes embarazadas que asisten al Centro de Salud Motupe - Palacio Lapo, Lia Michelle (2022)
Vaginal yeast infections is an imbalance caused mainly by the genus Candida spp. There are more than 200 strains of this microorganism, but only 10 are described as pathogens of clinical and research importance in humans since they alter the normal conditions of the microbiota of the female genital tract, most frequently affecting pregnant patients due to their physiological conditions and anatomical changes, which consequently can cause a rupture of membranes, contamination of the newborn at the time of delivery, postpartum infections, among others. In view of this situation, the interest arises to determine the presence and identify the serotypes and susceptibility of Candida spp. in vaginal secretion samples of pregnant patients attending the Motupe Health Center during the year 2022. For this purpose, the present study had a descriptive cross-sectional quantitative design, with a sample of vaginal secretion from 100 pregnant patients, who were transferred from the Motupe health center to the microbiology laboratory of the Faculty of Human Health, after having completed the pre-analytical phase, The samples were sown in Sabouraud culture medium and the cultures with significant growth were reseeded in CHROMagar-Candida and tested with the antifungigram. The results showed that the most frequently isolated species was the Candida albicans complex, followed by Candida tropicalis and Candida parapsilosis, with a 100% susceptibility profile to fluconazole and voriconazole. Translated with www.DeepL.com/Translator (free version)